The relationship between inflation and unemployment rate in Malaysia (Analysis of Phillips Curve in Malaysia) / Mohammad Shazwan Roselim - Roselim, Mohammad Shazwan (2019)
The negative coalition between unemployment and inflation is known as Phillips Curve because William Phillips introduced the trade-off relationship between these two variables in 1985. For many years, the Phillips Curve has been an important mechanism for macroeconomic policy formulators in many countries. Considering the fact that the majority of the research on Phillips Curve have been done in the context of the developed economies, this study focuses in Malaysia and aims to empirically analyse the relationship between unemployment rate and inflation rate in a developing country. The main finding of the current inquiry is that there existed an equilibrium relationship between unemployment rate and inflation rate in Malaysia. The results of this study will support the validity of the Phillips Curve hypothesis.